Multimodality Discourse Analysis of Cosmetic Products 3D Advertisement - Susandra, Englia Dwi Septi Metjra; Hamzah, Hamzah (Universitas Negeri Padang, 2024)
Multimodality discourse analysis is an approach that examines how meaning is formed by utilizing various modes of communication in social interactions. This research conducts a multimodal analysis of two Nature Republic video advertisements in collaboration with NCT 127; Sun BlockBuster and Hyalon Active 10 Serum. This study aims to find (1) the similarities and differences of the visual elements of both ads, (2) the similarities and differences of the verbal elements of both ads, and (3) the congruence between the visual and verbal elements of the videos. Utilizing theories from Kress & van Leeuwen (2006), Cheong (2004), Halliday & Matthiessen, (2014), and Leeuwen (2005), the study reveals that differences in visual elements dominate over similarities. The Sun BlockBuster ad emphasizes conceptual symbolic suggestive and narrative actional transactional elements, while the Hyalon Active 10 Serum ad features narrative actional non-transactional elements. Verbal analysis shows Sun BlockBuster utilizes more declarative moods, while Hyalon Active 10 Serum features more judgment in its verbal elements. Both ads exhibit marked contrasts in their thematic structures and the use of marked versus unmarked topical themes. The generic structure analysis of the two advertisements showed similarities in display, congruent, call and visit information, but differences in the generic structure analysis were found in three different sub-indicators: secondary announcement in Hyalon Active 10 Serum, enhancer, and tag owned by Sun BlockBuster. Information linking demonstrates shows that Sun BlockBuster focusing on elaboration and Hyalon Active 10 Serum on a fresh, clean aesthetic.